2014
DOI: 10.4103/0973-8258.126811
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and pharmacology ofTecomella undulata

Abstract: Tecomella undulata (Bignoniaceae) is a monotypic genus and one of the most important deciduous, ornamental shrub or small tree of the acrid zone of India. Locally known as Rohida, Roheda in Hindi, Rakhtroda in Marathi, Dadimacchada, Chalachhada, Dadimapuspaka in Sanskrit mostly found in the Thar desert regions of India and Pakistan. The plant holds tremendous potential of medicinal value and is used in traditional and folklore system of medicines. It has been used traditionally in various ailments like syphili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…With age, a decrease in elastin, collagen, and hyaluronic acid causes skin strength and flexibility loss, resulting in wrinkles. [6,9] External factors are still the most influential factor in the process of wrinkling. These external factors can be exposure to UV rays, unhealthy lifestyles, environmental pollution, radiation, cigarette smoke, and stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With age, a decrease in elastin, collagen, and hyaluronic acid causes skin strength and flexibility loss, resulting in wrinkles. [6,9] External factors are still the most influential factor in the process of wrinkling. These external factors can be exposure to UV rays, unhealthy lifestyles, environmental pollution, radiation, cigarette smoke, and stress.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in MMP-1 levels was around 4.4 ± 0.2 times compared to skin that was not exposed to UV radiation [4]. Matrix metalloproteinase-1 was chosen in this study because it is a subgroup of MMPs that play a role important in the photoaging processing collagenase with degradation of collagen types 1 and 2 resulting from direct UVA and UVB exposure with significantly increased regulation of these exposures compared to other types of MMPs, and most markedly increased when skin severity is present [6][7][8].…”
Section: Exposure To Sunlight (Ultraviolet Rays [Uv]mentioning
confidence: 99%
“…5,6 Several studies have reported that oxidative stress and the overproduction of reactive oxygen species (ROS) play an important role in the skin aging process. 2,7,8 The excessive exposure of skin to UV radiation can lead to the over-production of ROS, which in turn triggers the activity of enzymes such as elastase, collagenase, and other matrix metalloproteinases (MMPs). These enzymes are responsible for the degradation of the skin's extracellular matrix proteins such as collagen and elastin, which leads to the appearance of skin wrinkles and loss of skin flexibility and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Its peel, covering around 60% of fruit, is a rich source of ellagitannins, flavonoids and proanthocyanidin (Mirdehghan and Rahemi, 2007). Tecomella undulata, a deciduous shrub has tremendous medicinal and therapeutic potential (Rohilla and Garg, 2014), which is attributed to the presence of secondary metabolites (phytosterols, glycosides, tannins, phenolic compounds, flavonoids, saponins) in its heartwood, bark and leaf (Dhir and Shekhawat, 2012).…”
Section: Introductionmentioning
confidence: 99%